Efficiency enhancement of solar cell using mirror concentrator (BIBECHANA, 2024)
This research is done to find out a method by which the efficiency of a solar cell can be increased by using mirror concentrator to get a higher power and optimum efficiency. At first the sun lights are incident on the mirror concentrator made of plane glass and then the reflected rays are incident to the solar cell. Flat mirror concentrator (FMC) has been used to increase the incident irradiance on solar panel system by concentrating the sun light ray on it and then to improve the cell performance. A comparison is made for the same PV solar panel systems using single and triple flat mirror concentrator. It is a beneficial and important theory of solar power plant sector. It can be used in household and any kind of industrial area. The FMC consists of two flat mirrors made of glass, with dimensions (170cm × 80cm) enclosed by aluminum frame and inclined to an angle 55° with a solar panel (160cm × 120cm) tilted at 45° from the horizon. The results indicated that when the concentrator is used with the solar panel the efficiency increased by a factor of 4.52% to 11.34%. So, the increase in efficiency of the solar cell is 6.82%.